A Universal Theory of Pottery Production : Irving Rouse, Attributes, Modes, and Ethnography - Krause, Richard A., 1938- (Book collections on Project MUSE., 2016)
"Irving Rouse is considered the father of Caribbean archaeology and one of the most important archaeological theorists in the world. His analytical and classification practices have been adopted by archaeologists working in Europe, Africa, North America, South America, and the Caribbean. In 1939, Rouse introduced a distinction between artifact attributes and modes. Attributes are any observation the archaeologist wishes to make about artifact properties. Modes are any standard, custom, or belief to which the artisan conformed during the production or use of artifacts. According to Rouse, all modes are attributes but not all attributes are modes. Modes are properly patterned attributes. Many archaeologists do not understand the implications of this crucial distinction, which is carefully and fully explicated in this book. Then the explication is used to create a general theory of ceramic production that, when applied to a sample, produces an ethnographic account of its production. When used to supplement traditional systems of artifact classification it will add both substance and meaning. When applied to an appropriate range of ceramic samples it will generate a world-embracing ceramic ethnography. As an example of how the Rouse-based approach should be applied and in an attempt to detail the transition Rouse posited from the Saladoid to Ostinoid Ceramic Series, Krause uses a ceramic sample from the Paso del Indio site in Puerto Rico"--Provided by publisher